2008
DOI: 10.1371/journal.pone.0003373
|View full text |Cite
|
Sign up to set email alerts
|

MetaSim—A Sequencing Simulator for Genomics and Metagenomics

Abstract: BackgroundThe new research field of metagenomics is providing exciting insights into various, previously unclassified ecological systems. Next-generation sequencing technologies are producing a rapid increase of environmental data in public databases. There is great need for specialized software solutions and statistical methods for dealing with complex metagenome data sets.Methodology/Principal FindingsTo facilitate the development and improvement of metagenomic tools and the planning of metagenomic projects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
313
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 401 publications
(319 citation statements)
references
References 42 publications
1
313
0
4
Order By: Relevance
“…Unfortunately, this method did not allow us to model different error rates conditioned on different underlying bases, which we felt was important. We also considered several other software packages for modeling Illumina style reads, including metasim (Richter et al 2008), PEMer (Korbel et al 2009), ReSeqSim (Du et al 2009), SimNext (http://evolution.sysu.edu.cn/ english/software/simnext.htm), Flux Simulator (http://flux.sammeth. net/index.html), and Mason (part of the SeqAn package) (Döring et al 2008), all of which lack one or more of the criteria we desired.…”
Section: Read Simulationmentioning
confidence: 99%
“…Unfortunately, this method did not allow us to model different error rates conditioned on different underlying bases, which we felt was important. We also considered several other software packages for modeling Illumina style reads, including metasim (Richter et al 2008), PEMer (Korbel et al 2009), ReSeqSim (Du et al 2009), SimNext (http://evolution.sysu.edu.cn/ english/software/simnext.htm), Flux Simulator (http://flux.sammeth. net/index.html), and Mason (part of the SeqAn package) (Döring et al 2008), all of which lack one or more of the criteria we desired.…”
Section: Read Simulationmentioning
confidence: 99%
“…Thus, the rRNA sequences obtained from the SOLiD-3 data were not analyzed further and will not be discussed further here. Simulations performed by the method of Richter et al (2008) showed that the upper limit for unique mapping errors, when allowing three to five mismatches for 50-bp sequences, was B0.007 and 3.12% for non-uniquely mapped sequences (Supplementary Material and Supplementary Table S3). These are estimated upper limits because the simulated data includes rRNA sequences and other repeat sequences (for example, insertion sequences, transposases and other repeated sequences) that were actually removed (or were not counted) by the transcript mapping procedure used in this study.…”
Section: Solid-3 Sequencing and Transcription Of Photosynthesis Genesmentioning
confidence: 99%
“…2. Short reads of ~100 nt were simulated from the 7 selected complete genomes (at 10X coverage) using MetaSim [18] (Version 0.9.1). For simplicity, no sequencing errors were introduced in the simulation.…”
Section: Simulated Short Readsmentioning
confidence: 99%